Sustainable Prairie - Brian Obermeyer (Symphony in the Flint Hills, 2014)
Tallgrass prairie once blanketed approximately 170 million acres of North America, from Texas up into Canada and from Kentucky west into Kansas. Only about 4 percent of this once vast sea of grass remains, making tallgrass prairie the most altered ecosystem on the continent in terms of acres lost.
Keywords: tallgrass; grassland; prairie; nature; natural; Great Plains; sustainable; farming; modern; Greater Flint Hills; landscape; Kansas; fertile; soil; grazing; fire; burning; Native Americans; bison; buffalo; Konza; animals